2016
DOI: 10.20965/ijat.2016.p0244
|View full text |Cite
|
Sign up to set email alerts
|

Informatics to Support Tactics and Strategies in Curling

Abstract: This paper presents game information analysis by utilizing a digital scorebook system, as the first tool for curling informatics, which supports coaches and players in realizing smart tactics and strategies in the sport of curling. Our research project, called “Curling Informatics,” aims to develop an environment to support curling strategies and tactics by realizing methods to record game information, perform analysis, and provide visualization and sharing of the information.We found a significant correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In the next step, we have analyzed the data collected with the iCE application focusing on the relation between shot accuracy and game score. Masui analyzed iCE data and confirmed that there is a strong correlation between the difference in shot accuracies and the difference in game scores and that correlation between shot accuracy and game score differ with level of team or player (Masui et al, 2016).…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…In the next step, we have analyzed the data collected with the iCE application focusing on the relation between shot accuracy and game score. Masui analyzed iCE data and confirmed that there is a strong correlation between the difference in shot accuracies and the difference in game scores and that correlation between shot accuracy and game score differ with level of team or player (Masui et al, 2016).…”
Section: Introductionmentioning
confidence: 87%
“…In the first step, Masui et al developed a digital scorebook iCE which runs on a tablet computer to collect and analyze game information and they confirmed validity of the system (Masui et al, 2016). As one of the applications of iCE, it is possible to check the shot accuracy of each team or player based on collected information sequentially and visually.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations